إسهامات البوطي في مقصد العقيدة: دراسة تحليلية في كبرى اليقينيات الكونية: An Analytical Study of al-Buti’s Contribution to Maqsad al-‘Aqidah: Reflections from Kubra al-Yaqiniyyat al-Kawniyyah - Mahmood Hazae Almaliki, Methaq Sadeq; Ahmad, Ridzwan (Afkar: Jurnal Akidah dan Pemikiran Islam, 2018)
This article aims to explain the contribution of al-Buti in the maqasid ‘aqidah, particularly his discussion in his work, Kubra al-Yaqiniyyat al-Kawniyyah on the main objective of the ‘aqidah. Hence, it reveals issues uncovered by Muslim scholars when discussing the issues of ‘aqidah because of their stand that regard them as fundamental issues which were unchanged according to the changing times and places. It is hoped that this study will restore the dynamism and direction of the right discussion on ‘aqidah after the occurrence of past weaknesses. Accordingly, this study discusses al-Buti’s definition of maqasid and the main objective of ‘aqidah as explained in Kubra al-Yaqiniyyat al-Kawniyyah. Among the findings of this study is the Islamic law has a close relationship with the maqasid ‘aqidah. Therefore, the implementation of Islamic law will not be developed except by the unity of ‘aqidah which is the basis and main pillar of Islam. Maqasid ‘aqidah is an important milestone and a major weapon in confronting the challenges of various external ideologies that could threaten the intellect and clarity of Islamic thought.